Chemical characterization and antimicrobial activity of essential oils of salvia L. species - Pierozan,Morgana Karen (2009)
In this work, the essential oils of S. officinalis, S. sclarea, S. lavandulifolia and S. triloba were chemically analyzed by gas chromatography coupled to a mass spectrometry detector (GC/MSD), and their antimicrobial activity was tested against 10 microorganisms using the disk diffusion method and the Minimum Inhibitory Concentration (MIC) technique. The following major compounds were identified in the essential oils: α - and β-thujone, camphor and 1,8-cineole, except in S. sclarea, where linalool, linalyl acetate and α-terpineol were the major constituents. The antimicrobial activity showed significant differences (p < 0.05) only when obtained by the MIC method. Gram-positive microorganisms presented larger sensitivity for the essential oils. The lowest MIC was observed when Staphylococcus aureus was exposed to 2.31 mg.mL-1 of S. lavandulifolia essential oil, while the highest MIC value was obtained when Shigella flexneri was exposed to 9.25 mg.mL-1 of the same essential oil, thus demonstrating that this essential oil may be effective as a bacteriostatic agent against Gram-positive microorganisms.